IKLIM SEKOLAH DAN KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN BERKUALITAS DI MTS - Didit Darmawan; syifa fairuz (Hijri, 2026)
This study aims to analyze the contribution of school climate and teacher pedagogical competence to the quality of learning in Madrasah Tsanawiyah. Employing a qualitative literature review method with content analysis, this research synthesizes academic literature to develop a conceptual understanding of how both factors influence learning quality. The findings reveal that school climate contributes through positive interpersonal relationships, principal support, clear rules, academic culture, inclusive atmosphere, and physical and psychological safety. Pedagogical competence contributes through understanding student characteristics, effective instructional design and implementation, mastery of subject matter, communication skills, classroom management, comprehensive evaluation, learning difficulty diagnosis, student potential development, meaningful learning creation, reflective practice, adaptation to change, collaboration, and commitment to continuous professional development. Optimal learning quality is achieved when positive school climate and strong pedagogical competence exist simultaneously and reinforce each other. The study implies that efforts to improve learning quality must address both factors in an integrated manner. Future research is recommended to conduct empirical studies testing the relationship among these variables, while madrasah managers are advised to regularly evaluate school climate and map teacher competence as a basis for designing targeted improvement programs